The Influence of Management Accounting Information System Characteristics, Utilization of Information Technology, and Accounting Knowledge on Managerial Performance (A Case Study at PT Nuansa Dharma Cipta) - Drajat, Muhammad Agung; Irwansyah, Irwansyah (CV. Inara, 2024)
The purpose of this study is to ascertain how managerial performance is impacted by the features of management accounting information systems, information technology use, and accounting expertise. kind of study that is quantitative. The sample consists of 40 managers who are respondents, while the research population consists of all managers of PT Nuansa Dharma Cipta Samarinda. Questionnaires and observations are used in data collection methods. Multiple linear regression, correlation and determination tests, as well as t and ui F tests, are the analytical instruments utilized. The study's findings demonstrate that all three independent variables management accounting information systems, information technology use, and accounting knowledge have a substantial impact on managerial performance at the same time. A partial test indicates that Managerial Performance is significantly and favorably impacted by the Management Accounting Information System. It is also claimed that information technology adoption significantly and favorably affects managerial performance. Similarly, PT Nuansa Dharma Cipta Samarinda's managerial performance is significantly impacted by accounting expertise.